PSYCHOLOGICAL AND HYGIENIC ESSENCE OF MOTIVATIONAL AND INTELLECTUAL READINESS OF CHILDREN FOR SYSTEMATIC EDUCATION IN SCHOOL - Мізюк, М. І.; Суслик, З. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article deals with the interpretation of the terms readiness to learn at school, motivational readiness, school maturity, the essence of the problem of motivational readiness for school. On the basis of the hygienic valuing of the social everyday life modern school environment, the state of health, containing physical, biological and psychophysiological development of the children; the peculiarities of the school maturity are determined. A morphofunetional state and level of biological development of the examined children is determined. The main sndices of the child readiness for studying at school are settled. The tables for the combined valuation of the physical development of the children at the first year of studying are worked out and scientifically substantiated.